The impact of community psychological responses on outbreak control for severe acute respiratory syndrome in Hong Kong. Issue 11 (4th November 2003) - Leung, G M; Lam, T-H; Ho, L-M; Ho, S-Y; Chan, B H Y; Wong, I O L; Hedley, A J
Abstract : Objective: To examine the public's knowledge and perception of SARS and the extent to which various precautionary measures have been adopted. Design: Cross sectional survey. Setting: General population of Hong Kong at the height of the SARS outbreak (29 March to 6 April 2003). Participants: 1115 ethnic Chinese adults. Main results: Forty per cent did not recognise fomites as a possible mode of transmission whereas 55.1% believed that the infection could be transmitted airborne. A large proportion (30.1%) believed they were very or somewhat likely to contract SARS while only one quarter believed they were very likely to survive if they contracted the disease, benchmarked against an actual case fatality ratio of 2.8% at the time of the survey and 15%–20% according to current best estimates. Precautionary measures directed against person to person droplet spread were generally adopted by most while the prevention of transmission through fomites was not practised as frequently. Respondents with higher risk perceptions and a moderate level of anxiety were most likely to take comprehensive precautionary measures against the infection, as were older, female, more educated people as well as those with a positive contact history and SARS-like symptoms. Conclusions: The findings demonstrate that the promotion of protective personal health practices to interrupt the self sustaining transmission of the SARS virus in the community must take into account background perceptions of risk and anxiety levels of the public at large. Continuing public education about preventive measures should be targeted at the identified groups with low current uptake of precautions.